Perbandingan Tektonika Pembentuk Sistem Modul Ruang di Rumah Vernakular Madura dan Sumba Barat - Alvin Febrian; Altrerosje Asri; Cynthia Santoso (ATRIUM: Jurnal Arsitektur, 2024)
Title: Comparison of Tectonics Forming Space Module Systems in Madurese and West Sumba Vernacular Houses Taneyan Lanjhang is a type of residential pattern in Madura, inhabited by one large family and consisting of several mass structures and a courtyard in the middle, one of which is the Roma Bangsal building intended as a residence for women.  Due to limited land, the designed module system must meet internal users’ needs and capacity. This research aims to compare and discover what factors influence the formation of spatial module systems from the tectonics through anthropometric dimensions in the form of residents' daily activities and social activities in Roma Bangsal, Bangsal gabung. As a comparison, Uma Mbatangu houses are used in Ratenggaro village, West Sumba.  The analysis method was carried out descriptively and qualitatively. Data collection uses a literature study method that visualizes plans, sections, and details. Roma Bangsal and Uma Mbatangu have unique architectural elements, especially the form and connection system. The similarity between the three in virtual aspects such as social strata (gender), light, empty, openness, and physical aspects, including materials, daily activities, scale, and proportion influencing how the connection to the module system creates the external appearance of the building, structure and indoor plan to create matters of integration.